Hippocampal PPARα is a novel therapeutic target for depression and mediates the antidepressant actions of fluoxetine in mice. (3rd June 2018) - Song, Lu; Wang, Hao; Wang, Ying‐Jie; Wang, Jin‐Liang; Zhu, Qing; Wu, Feng; Zhang, Wei; Jiang, Bo
Abstract : Background and Purpose: Developing novel pharmacological targets beyond the monoaminergic system is now a popular strategy for treating depression. PPARα is a nuclear receptor protein that functions as a transcription factor, ‐regulating gene expression. We have previously reported that both WY14643 and fenofibrate, two pharmacological agonists of PPARα, have antidepressant‐like effects in mice, implying that PPARα is a potential antidepressant target. Experimental Approach: We first used various biotechnological methods to evaluate the effects of chronic stress and fluoxetine on hippocampal PPARα. The viral‐mediated genetic approach was then employed to explore whether hippocampal PPARα was an antidepressant target. PPARα inhibitors, PPARα‐knockout (KO) mice and PPARα‐knockdown (KD) mice were further used to determine the role of PPARα in the antidepressant effects of fluoxetine. Key Results: Chronic stress significantly decreased mRNA and protein levels of PPARα in the hippocampus, but not other regions, and also fully reduced the recruitment of hippocampal PPARα to the cAMP response element‐binding (CREB) promoter. Genetic overexpression of hippocampal PPARα induced significant antidepressant‐like actions in mice by promoting CREB‐mediated biosynthesis of brain‐derived neurotrophic factor. Moreover, fluoxetine notably restored the stress‐induced negative effects on hippocampal PPARα. Using PPARα antagonists fully blocked the antidepressant effects of fluoxetine in mice, and similarly, both PPARα‐KO and PPARα‐KD abolished the effects of fluoxetine. Besides, PPARα‐KO and PPARα‐KD aggravated depression in mice. Conclusions and Implications: Hippocampal PPARα is a potential novel antidepressant target that mediates the antidepressant actions of fluoxetine in mice.